Batman : the long Halloween - Loeb, Jeph (DC Comics, 2025)
"Every Day Is Halloween... A costumed hero learning he can trust no one. A crime lord trying to hold on to a crumbling empire. An honest district attorney hiding a terrible secret. And a friendship that would be shattered forever. These are the pieces of the murder mystery The Long Halloween. Batman: The Long Halloween is created by the Eisner Award-winning team of Jeph Loeb and Tim Sale (authors of Superman for All Seasons, Catwoman: When in Rome, and Batman: Haunted Knight). This compelling look into the Dark Knight's early career features some of the most deadly and cunning members of Batman's rogues gallery, and a dramatic retelling of the origin of the tragic villain Two-Face!"-- Provided by publisher.